2008 IEEE International Symposium on Signal Processing and Information Technology 2008
DOI: 10.1109/isspit.2008.4775668
|View full text |Cite
|
Sign up to set email alerts
|

Denoising and Image Compression Using Bspline Wavelets

Abstract: II. Bspline Based Wavelet Family In this paper we briefly describe the results of a recent In [7], a Bspline-based semi-orthogonal wavelet family research on how to construct and implement Bspline ' th waveet asi.Nxt,a nvel echiqu baed n uing has been constructed. It has been shown that the mh wavelet basis. Next, a novel technique based on using odrBpieplnma m( i aife h Bspline wavelet basis, is proposed for signal de-noising and image compression. Extensive simulation results, following 2-scale relation have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 6 publications
0
4
0
11
Order By: Relevance
“…As in the case of shape analysis, distances from representative atoms between 15 residues surrounding the pocket were measured to find the best correlation of distances with K d,STU . Multiple linear regression was performed using the program xlstat ( 26 ) to find the best equation relating the distances measured between the centre points near the ends of the side chains (see Appendix S2 ) and log 10 K d,STU . Amino acid residues used to create these distance descriptors were extracted by referring to PKA equivalent residues from the ClustalX ( 27 ) multiple sequence alignment of the 113 kinases in Fabian’s data set ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…As in the case of shape analysis, distances from representative atoms between 15 residues surrounding the pocket were measured to find the best correlation of distances with K d,STU . Multiple linear regression was performed using the program xlstat ( 26 ) to find the best equation relating the distances measured between the centre points near the ends of the side chains (see Appendix S2 ) and log 10 K d,STU . Amino acid residues used to create these distance descriptors were extracted by referring to PKA equivalent residues from the ClustalX ( 27 ) multiple sequence alignment of the 113 kinases in Fabian’s data set ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the wavelet basis, is proposed for signal de-noising and image compression. [8]…”
Section: Influence Of the Wavelet Family In The Compression-denoisingmentioning
confidence: 99%
“…Kap. 6 greift in dieser Stoßrichtung Arbeiten auf, die in den IB, vor allen Dingen an den Rändern der Disziplin 38 , durchaus existieren, allerdings eher neben dem, teils in offener Abgrenzung zum mehrheitsfähigen Sozialkonstruktivismus. Attraktiv erscheint bei einigen dieser Arbeiten, dass Prozesse der Bedeutungsschaffung als zentrales Problem ausgemacht werden.…”
Section: Vorwort Zur Buchausgabe Und Danksagungunclassified